Oral direct renin inhibitor aliskiren reduces in vivo oxidative stress and serum matrix metalloproteinase-2 levels in patients with permanent atrial fibrillation - Yoshizumi Takei, MD; Minoru Ichikawa, MD, PhD; Yoshiyuki Kijima, MD, PhD (Journal of Arrhythmia, 2015)
We aimed to determine the effects of the oral direct renin inhibitor aliskiren on in vivo oxidative stress in atrial fibrillation (AF) patients. In this study, 150 mg oral direct renin inhibitor aliskiren was administered once daily to 12 permanent AF patients. Aliskiren significantly reduced urinary excretion of the oxidative stress biomarker 8-iso-prostglandin F2α and serum levels of matrix metalloproteinase-2(MMP-2). We concluded that aliskiren reduces in vivo oxidative stress and serum MMP-2 levels in patients with permanent AF.